IDENTIFICATION OF LEARNING MODELS THAT CAN AFFECT LINGUISTIC INTELLIGENCE OF ELEMENTARY SCHOOL STUDENTS - Anik Dwi Febrianti; Ingke Joanna; Dyah Rahayu Restiana Putri; Conny Dian Sumadi (Citra Dharma Cindekia, 2022)
Linguistic intelligence is one example of a person's multiple intelligences in terms of reading, writing, and listening. Based on the data obtained, overall, Indonesia's national alibaca index is included in the low literacy category. Because reading is an aspect of linguistic intelligence, this shows that efforts to develop students' linguistic intelligence in Indonesia are still low. This study aims to identify what learning models can affect the linguistic intelligence of elementary school students. This research takes several sources of scientific journals that are relevant to the research content. The research method used in this research is library research. The material obtained will be identified, presented, and described descriptively. The results of this study indicate that there are 3 learning models that can affect the linguistic intelligence of elementary school students, namely the two stay two/three stray cooperative model (TS TS), the round club model (around the group), and contextual learning (CTL). The three models have gone through the previous research process and have been validated so that they can be applied to research subjects.